Analysis of Factors influencing the successful use of Massive Open Online Courses (MOOCs) to prepare Digital Talent - Muh Syaiful Romadhon; Betty Purwandari; Imairi Eitiveni; Mardiana Purwaningsih (Journal of Educational Science and Technology (EST), 2023)
One type of e-learning category is Massive Open Online Courses (MOOCs). MOOCs or MOOC promote the "democratization of education" that allows education to be accessed by everyone from anywhere and anytime. The use of MOOCs gives students access to a wide variety of resources. MOOs enable students to have the sufficient storage capacity to store their materials. MOOCs have the potential to improve digital capabilities in the face of digital transformation. The intention to use MOOC is relatively high, however, in terms of class completion rate and motivation to pass on MOOC is relatively low. These conditions need to be examined to increase the success rate of MOOCs usage. This research develops a model and identifies factors that influence the successful use of MOOCs to prepare digital talent. The approach is a mixed method that collects quantitative data using an online questionnaire and qualitative data via interviews. The researcher took data from 91 samples and eight informants for interviews. In the study results, 6 out of 12 hypotheses are accepted in this study. The factors that influence a person in completing MOOC either directly or indirectly include Performance expectancy, willingness to earn certificates, MOOC quality, and Intrinsic motivation. This research also produces recommendations that can be used as consideration for parties related to MOOC.